A semiotic approach to grammaticalization: modelling representational and interpersonal modality expressed by verbonominal patterns. (May 2022) - Davidse, Kristin; Van linden, An; Brems, Lieselotte
Abstract: This paper develops a framework capable of analysing modal qualifications coded by both canonical modal markers and grammaticalized expressions within a semiotic grammar approach (McGregor, 1997). We focus on grammatical constructions that developed from complement constructions containing the shell nouns need, way, chance, doubt, question and wonder, often preceded by a negative quantifier. We range the different types of modal qualification in a hierarchy. The top half subsumes mirativity and epistemic modality, which scope over propositions, and interpersonal deontic modality, which scopes over processes. The bottom half contains representational deontic and dynamic modality, which are internal to the proposition. We also address the neglected issue of the presence of polarity choices in the modal qualifications and in the propositions and processes. In particular, we argue that epistemic modality ascribes inherently positive degrees of likelihood to either positive or negative propositions, thus assessing the probability of occurrence versus non-occurrence of temporally located processes. This allows us to explain not only the semantic equivalence involved in NEG-raising, as in I think he did nothing wrong and I don't think he did anything wrong, but also, more broadly, between pairs like there's no chance she will cry and there's no doubt she will not cry . Finally, the proposed semantic model puts us in a position to propose structural analyses of the interpersonal and representational qualifications of propositions and processes within the broad outlines of McGregor's (1997) Semiotic Grammar. Highlights: Shell nouns ( chance/doubt/need/way/wonder/question ) + complement as source construction for lexical and grammatical meanings. Further underpinning of two grammaticalization paths of modal meanings: auxiliarization and nucleus-margin reversal of complex sentences. Account of availability of polarity choices in systems of epistemic, deontic and dynamic modality and in units they apply to. Account of epistemic modality as ascribing positive degrees of likelihood to either positive or negative proposition. Interpersonal and representational meanings call for distinct structural analyses, viz. scoping vs. compositional dependency.